Provincial Solidarities: The Early Years of the New Brunswick Federation of Labour, 1913–1929 - Frank, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractThis study draws attention to the importance of the early provincial federations of labour as a distinct form of labour organization in early 20th-century Canada. One of the first of these was the New Brunswick Federation of Labour, which attempted to strengthen local bonds of solidarity and represent workers at the level of the provincial state. The Federation originated with and was dominated by male workers in the skilled trades in the largest cities and by 1921 attracted almost 100 delegates from nine population centres, including a small number of women and Acadians. Its agenda included campaigns for the enactment of workers' compensation, the protection of women workers and the election of labour candidates, but a more thoroughgoing Reconstruction Programme (1919) was less successful, especially in the context of regional economic crisis in the 1920s. The study confirms the existence of a progressive movement within provincial society while identifying the limited scope of its ambitions and achievements. This study uses social history methods to explore an institutional narrative and to analyze a distinct chapter in the history of organized labour at the provincial level.